Circadian effects on stroke outcome – Did we not wake up in time for neuroprotection?. Issue 3 (March 2021) - Boltze, Johannes; Didwischus, Nadine; Merrow, Martha; Dallmann, Robert; Plesnila, Nikolaus
The occurrence of stroke in humans peaks in the morning. A recent study revealed that time of day mitigates the therapeutic impact of neuroprotective paradigms. These findings might not only explain the previous failure of translation of neuroprotective therapies but inspire new paradigms in stroke chronopathophysiology research. Taking chronotype into account may complement the many factors that influence efficacy of experimental therapies in stroke.